Effect of hypoxia-induced mIL15 expression on expansion and memory progenitor stem-like TILs in vitro - Sun, Zhen; Xu, Aotian; Wu, Zhaojun; Lan, Xiaohao; Gao, Ganchen; Guo, Bin; Yu, Zhongjie; Shao, Lin; Wu, Hao; Lv, Min; Wang, Yongjie; Zhao, Yi; et al. (Frontiers in Immunology, 2024)
IntroductionThe adoptive cell transfer of tumor-infiltrating lymphocytes (TILs) has proven clinically beneficial in patients with non-small cell lung cancer refractory to checkpoint blockade immunotherapy, which has prompted interest in TIL-adoptive cell transfer. The transgenic expression of IL15 can promote the expansion, survival, and function of T cells ex vivo and in vivo and enhance their anti-tumor activity. The effect of expressing mIL15 regulated by hypoxia in the tumor microenvironment on the expansion, survival, and stem-like properties of TILs has not been explored.MethodsUsing TILs expanded from the tumor tissues of lung cancer patients, TILs with or without mIL15 expression (TIL-mIL15 or UN-TIL) were generated by lentiviral transduction. To reflect the advantages of mTIL15, the cells were divided into groups with IL2 (TIL-mIL15+IL2) or without IL2 (TIL-mIL15-IL2).ResultsCompared to UN-TIL cells, mIL15 expression had a similar capacity for promoting TIL proliferation and maintaining cell viability. Our experimental findings indicate that, compared to UN-TIL and TIL-mIL15+IL2 cells, the expression of mIL15 in TIL-mIL15-IL2 cells promoted the formation of stem-like TILs (CD8+CD39-CD69-) and led to significant decreases in the proportion and absolute number of terminally differentiated TILs (CD8+CD39+CD69+). RNA-Seq data revealed that in TIL-mIL15-IL2 cells, the expression of genes related to T cell differentiation and effector function, including PRDM1, ID2, EOMES, IFNG, GZMB, and TNF, were significantly decreased, whereas the expression of the memory stem-like T cell marker TCF7 was significantly increased. Furthermore, compared to UN-TIL and TIL-mIL15+IL2 cells, TIL-mIL15-IL2 cells showed significantly lower expression levels of inhibitory receptors LAG3, TIGIT, and TIM3, which was consistent with the RNA-Seq results.DiscussionThis study demonstrates the superior persistence of TIL-mIL15-IL2 cells, which may serve as a novel treatment strategy for lung cancer patients.